Developing Problem High Order Thinking Type Application Volume Cube and Cuboid Based Problem Based Learning for Secondary School - Marlina, Eli; Putri, Ratu Ilma Indra; Darmawijoyo, Darmawijoyo (International Journal of Active Learning, 2019)
This research aim to develop a valid and practical problem High Order Thinking Type Application Volume Cube and Cuboid based Problem Based Learning for secondary school. This is a development studies with formative evaluation type. Data collection technique include walk through, documentation, interview, test, and questionnaires. The prototype is valid qualitatively by validators that are expert. In aditonal expert have also stated that prototype is practical problem for. It has also been tested to eight grade student to know the quantitative validity and reliability of each item. This study result fifteen item exam high order thiking type application volume cube and cuboid based problem based learning for eight grade student.